The evolution of dust in the local and high-redshift universe. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Dwek, Eli; Arendt, Richard G.; Staguhn, Johannes; Temim, Tea
Abstract: Dust is a ubiquities component of the interstellar medium (ISM) of galaxies, and manifests itself in many different ways. Yet, its origin, composition, and size distribution are still a matter of great debate. Most of the thermally condensed dust is produced in the explosively expelled ejecta of core collapse supernovae (CCSNe) and in the quiescent winds of AGB stars. Following its injection into the ISM it is destroyed by supernova (SN) shock waves. Knowing the relative rates of these processes is crucial for understanding the nature and evolution of dust in galaxies. In the following we will review three aspects of the evolution of dust in galaxies: the evolution of dust in the ejecta of SN1987A; the rates of dust production and destruction rates in the Magellanic Clouds (MCs), and the evolution of dust in CLASH 2882, a gravitationally-lensed galaxy at z =1.